Plant Molecular Farming – Integration and Exploitation of Side Streams to Achieve Sustainable Biomanufacturing - Buyel, Johannes F. (Frontiers in Plant Science, 2019)
Plants have unique advantages over other systems such as mammalian cells for the production of valuable small molecules and proteins. The benefits cited most often include safety due to the absence of replicating human pathogens, simplicity because sterility is not required during production, scalability due to the potential for open field cultivation with transgenic plants, and the speed of transient expression potentially providing gram quantities of product in less than 4 weeks. Initially there were also significant drawbacks, such as the need to clarify feed streams with a high particle burden and the large quantities of host cell proteins, but efficient clarification is now readily achieved. Several additional advantages have also emerged reflecting the fact that plants are essentially biodegradable, single-use bioreactors. This article will focus on the exploitation of this concept for the production of biopharmaceutical proteins, thus improving overall process economics. Specifically, we will discuss the single-use properties of plants, the sustainability of the production platform and the commercial potential of different biomass side streams. We find that incorporating these side streams through rational process integration has the potential to more than double the revenue that can currently be achieved using plant-based production systems.